Synthesis of Some New Quinazoline-4-(3H)-ones and Styryl Hemicyanines as Possible Antimicrobial Agents - AFSAH, S.A.; AHMAD, JAWAID; PURBEY, R.; KUMAR, A. (Asian Journal of Chemistry, 2010)
In the present note we report the synthesis of some new quinazoline- 4 (3H)-ones and styryl hemicyanines as possible antimicrobial agents.